Penerapan Model Pembelajaran Kooperatif Tipe Make a Match untuk Meningkatkan Prestasi Belajar Siswa Kelas III A SDN 38 Kota Bengkulu - Akhiri Putri; Johanes Sapri; Herman Lusa (JURIDIKDAS, 2020)
This study aims to improve student learning achievement in Thematic learning class III A SDN 38 Bengkulu City by applying the Cooperative learning model type Make a Match. The subjects of the study were students of class III A SDN 38 Bengkulu City. The research instruments were observation sheets and test sheets. The observation data analysis technique used the formula of average score, highest score, lowest score, difference in score, and range of values for each criterion. Test data were analyzed using the formula of the average value and the percentage of classical learning completeness. Thus the application of the Make a Match type Cooperative learning model can improve student learning achievement in Thematic learning class III A SDN 38 Bengkulu City